Study of two-photon absorption and optical limiting - Ghimire, Bal Ram (BIBECHANA, 2021)
Simultaneous absorption of two photons of identical or different frequencies to excite a system that is atom or molecule from the ground state to excited state has great importance. It has an important role as a spectroscopic tool for determining the positions of energy levels that are not connected to the atomic ground state by the one-photon transition. In this work, experimental study of two-photon absorption of fused silica, quartz crystal, and metal halides and optical limiters based on the semiconductors are studied. It was investigated that two photons absorption depletes the transmitted beam but carrier defocusing spreads the beam in space and hence density is reduced. It was realized that limiters with thin samples have low dynamic range and fluency is high on the damage-prone surface and irreversible damage occurs. Some Semiconductors with high nonlinearity are found to be useful materials for optical limiters to protect devices like sensors. BIBECHANA 18 (2) (2021) 26-31